"Click" reaction mediated synthesis of costunolide and dehydrocostuslactone derivatives and evaluation of their cytotoxic activity. Issue 11 (1st November 2016) - Pavan Kumar, Ch.; Devi, A.; Ashok Yadav, P.; Rao Vadaparthi, R.; Shankaraiah, G.; Sowjanya, P.; Jain, Nishant; Suresh Babu, K.
Abstract: As part of pharmacological–phytochemical integrated studies on medicinal plants from Indian flora, costunolide (1 ) and dehydrocostus lactone (2 ), were isolated as major phytochemicals from Saussurea lappa, a plant traditionally used in different Asian systems of medicine. A series of 1, 4-disubstituted-1, 2, 3-triazoles conjugates were synthesized through diastereo selective Michael addition followed by regioselective Huisgen 1, 3-dipolar cycloaddition reactions. All these triazolyl derivatives (5a –5j ) & (7a –7j ) were well characterized using modern spectroscopic techniques and evaluated for their anticancer activity against a panel of five human cancerous celllines. The results indicated that all the analogs displayed moderate cytotoxic activity. Graphical abstract: